Building the capacity of frontline workers to improve IYCF practices among marginalized communities in Odisha - Bhattacharjee, Sourav; Tripathy, Lopamudra; Choudhury, Prajna (International Food Policy Research Institute, 2015)
Evidence shows that consistent and systematic interpersonal communication (IPC) is critical to changing infant and young child feeding (IYCF) practices (UNICEF 2013). Using this evidence, UNICEF designed videos to enhance the capacity of frontline workers to provide correct information and appropriate counseling on IYCF. The assumption is that building the capacity of frontline workers will lead to increased counseling, improved knowledge, and changes in practices among mothers and caregivers.